2015
DOI: 10.15640/ijn.v2n1a14
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness Assertive Training of Bullying Prevention among Adolescents in West Java Indonesia

Abstract: Background: School bullying is an aggressive behavior which tend to harm another in school environment. The incidents of bullying among adolescents happened in yunior high school was 66.1%. Generally adolescents who could not developed their assertiveness, will tend to be aggressive. Methods: A Quasi experimental pre-post test with control group was conducted among the adolescents the total subjects studied was 80. Data were analyzed by using SPSS (version 19). Results & Conclusion: the sample were randomized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 5 publications
(6 reference statements)
3
17
1
2
Order By: Relevance
“…This is must be a concern of health workers, including nurses. [5] explained that interventions to overcome the problem of bullying victims for school adolescents can be done through the implementation of a program that focuses on children's ability to solve problems, overcome anger, self-control, understand their feelings, social abilities, and communication ability because of the main characteristics of bullying victims are students who have low assertiveness. Individuals who have a low assertiveness have many irrational fears, including often experiencing ICHT 2019 anxiety and not having the ability to defend their personal rights.…”
Section: Introductionmentioning
confidence: 99%
“…This is must be a concern of health workers, including nurses. [5] explained that interventions to overcome the problem of bullying victims for school adolescents can be done through the implementation of a program that focuses on children's ability to solve problems, overcome anger, self-control, understand their feelings, social abilities, and communication ability because of the main characteristics of bullying victims are students who have low assertiveness. Individuals who have a low assertiveness have many irrational fears, including often experiencing ICHT 2019 anxiety and not having the ability to defend their personal rights.…”
Section: Introductionmentioning
confidence: 99%
“…It is a negative action when someone intentionally inflicts, or attempts to inflict injury or discomfort upon another In Indonesia, gender-based bullying in educational institutions is also evident. A number of research studies have demonstrated an increasing pattern of the phenomenon in various contexts (Hinitz et al 2010;Keliat et al 2015;Mahmud et al 2014;Vambheim 2010). Most of the research focuses on the bullying that takes place in high schools.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these descriptions, the juvenile delinquency could be minimized by providing assertive training in behavioral counseling techniques (Boket, Bahrami, Kolyaie, & Hosseini, 2016;Parray & Kumar, 2017;Puri & Luqman, 2015). Counseling involves helping people through the process of interaction of a personal nature between the counselor and the counselee, counselee able to understand themselves and their surroundings, able to make decisions and set goals based on common values that so that counselees feel happy and effective behavior (Boket et al, 2016;Keliat, Tololiu, Daulima, & Erawati, 2015;Schry & White, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Assertive training is given to individuals who disturbed anxiety, unable to defend their rights, too weak, let others push him, not be able to express anger properly and quickly offended. Assertively constitute an ability to communicate what they want, feel and think about other people while maintaining and respecting the rights and feelings of others (Boket et al, 2016;Keliat et al, 2015;Parray & Kumar, 2017). The basic assumption of assertiveness training is that every person has the right to her feelings, opinions, what is believed and attitudes towards others with respect and to respect the rights of the person.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation